HUBUNGAN ANTARA MINDFULNESS DAN PEMBELIAN IMPULSIF PADA REMAJA PEREMPUAN YANG MELAKUKAN SHOPPING ONLINE - Teguh Lesmana (Psibernetika, 2017)
As the development of technology and internet facilities many items can be purchased online. Indonesia has in recent years experienced an increase in purchases of goods online and most of these online transactions are done by women. The facilities provided by online stores often make people more comfortable shopping online. Ease of shopping can trigger the occurrence of purchases that are often not based on the needs and only based on impulse. A person can shop for the needs and motivation of shopping itself. Feelings and emotions are influenced by the human mindset and mindset can relate to one's mindfulness condition. Mindfulness becomes important for online shopping activities, because if a person is not fully aware of the shopping behaviors performed then the shopping behavior becomes something that happens automatically. Shopping behavior that happens automatically will lead someone to make purchases impulsively. The purpose of this study was to find out the relationship between mindfulness and impulsive purchases in girls. Research participants were 228 adolescent girls from University X in West Jakarta. This research uses quantitative method of correlational research type. Correlation test uses Pearson correlation because data is normally distributed. The conclusion in this study is mindfulness has a significant relationship with impulsive purchases in adolescent girls who do shopping online (p <0.01). The direction of mindfulness and impulsive relationship is negative, which means that the higher the mindfulness the impulse buying tendency will be lower. Keywords: Mindfulness, impulsive purchase, online shopping